Film marketing action plan for film-induced tourism destinations: the case of the Island of Sao Nicolau - Nogueira, Sónia P. (2019)
The objective of the present work was to elaborate an action plan of a marketing film for the promotion of tourism in the Island of São Nicolau in Cape Verde, in order of establishing, through one of the new found ways of innovation in tourism in relation to convention methods, establish with the target audience a relationship of greater effectiveness and coverage as far as film-induced tourism is concerned. São Nicolau island is recognized as being the birthplace of the Cape Verdean intelligentsia and as an island with deep historical and cultural roots. Based on the national recognition and opting for a distinct promotion of the others, the promotional video emphasized the three typologies- cultural, historical and ecological, leaving aside the much abused sun and sea.